Genetic Liability to Higher Muscle Strength Associates With a Lower Risk of Cardiovascular Disease Mortality in Men Irrespective of Leisure‐Time Physical Activity in Adulthood: A Longitudinal Cohort Study - Päivi Herranen; Katja Waller; Laura Joensuu; Teemu Palviainen; Eija K. Laakkonen; Jaakko Kaprio; Elina Sillanpää (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Low muscle strength predicts premature mortality. We determined whether genetic liability to muscle strength is associated with mortality and whether this association is influenced by long‐term leisure‐time physical activity (LTPA). Methods and Results We estimated the effects of a polygenic score for handgrip strength (PGS HGS) on all‐cause and cardiovascular disease (CVD) mortality risk in the older Finnish Twin Cohort (N=8815, 53% women). LTPA was assessed longitudinally using validated questionnaires. During the 16.9‐year median follow‐up (143 723 person‐years), 2896 deaths occurred, of which 1089 were attributable to CVD. We found a significant interaction between sex and PGS HGS (P=0.016) in relation to all‐cause mortality. In men, 1‐SD increase in the PGS HGS was associated with a decreased risk of all‐cause (hazard ratio [HR], 0.93 [95% CI, 0.89–0.98]) and CVD mortality (HR, 0.88 [95% CI, 0.81–0.96]), but was not statistically significantly associated with mortality in women (HR, 1.01 [95% CI, 0.96–1.07]; and HR, 0.96 [95% CI, 0.87–1.05], respectively). In men, associations remained after adjusting for LTPA and persisted for CVD mortality (HR, 0.85 [95% CI, 0.76–0.96]), even after accounting for other lifestyle covariates. This remained statistically significant even when non‐CVD death was accounted for as a competing risk event. No PGS HGS×LTPA interactions were found. The predictive area under the curve estimates for PGS HGS alone were limited (0.53–0.64) but comparable to that of several lifestyle factors. Conclusions Higher PGS HGS was associated with a decreased risk of CVD mortality in men. Long‐term LTPA in adulthood did not potentiate this association.